2012
DOI: 10.4103/0970-0218.96093
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the burden of disease from unsafe injections in India: A cost-benefit assessment of the auto-disable syringe in a country with low blood-borne virus prevalence

Abstract: Background:Unsafe medical injections are a prevalent risk factor for viral hepatitis and HIV in India.Objectives:This review undertakes a cost–benefit assessment of the auto-disable syringe, now being introduced to prevent the spread of hepatitis B virus, hepatitis C virus, and human immunodeficiency virus (HIV).Materials and Methods:The World Health Organization methods for modeling the global burden of disease from unsafe medical injections are reproduced, correcting for the concentrated structure of the HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Intravenous drug use is the predominant mode of transmission of HCV in several developed countries, however in developing countries, the main modes of transmission are transfusion of infected blood and its components and surgical, dental procedures with improperly sterilized instruments and unsafe therapeutic injections with reused syringes. 38% of HCV infection in India may be attributable to unsafe therapeutic injections (19) In our study, past history of surgical procedures was found in majority of patients which is consistent with the findings of a study from Pakistan in which previous vaginal deliveries with episiotomy, previous surgeries, previous blood transfusion and Previous Dilatation and Curettage for abortion or Dysfunctional Uterine Bleeding were taken as independent variables, Only past history of surgical procedures was found to be the most important risk factor for transmission of H.C.V (20) In present study, previous blood transfusion as important risk factor for transmission of HCV infection was observed in 8% of patients. Blood transfusion is also reported to be a major source of HCV infection in a study from Hazra, Pakistan (21) Our study showed that about 42 % of anti-HCV positive women had no identifiable risk factors for HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous drug use is the predominant mode of transmission of HCV in several developed countries, however in developing countries, the main modes of transmission are transfusion of infected blood and its components and surgical, dental procedures with improperly sterilized instruments and unsafe therapeutic injections with reused syringes. 38% of HCV infection in India may be attributable to unsafe therapeutic injections (19) In our study, past history of surgical procedures was found in majority of patients which is consistent with the findings of a study from Pakistan in which previous vaginal deliveries with episiotomy, previous surgeries, previous blood transfusion and Previous Dilatation and Curettage for abortion or Dysfunctional Uterine Bleeding were taken as independent variables, Only past history of surgical procedures was found to be the most important risk factor for transmission of H.C.V (20) In present study, previous blood transfusion as important risk factor for transmission of HCV infection was observed in 8% of patients. Blood transfusion is also reported to be a major source of HCV infection in a study from Hazra, Pakistan (21) Our study showed that about 42 % of anti-HCV positive women had no identifiable risk factors for HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…[81][82][83] The estimated median population attributable fraction for chronic hepatitis B linked to injections in India was 46% while that for hepatitis C and HIV was 38% and 12% respectively. 84 …”
Section: Unsafe Injection Practicesmentioning
confidence: 99%
“…83 It has been estimated that 38% of HCV infections in India may be attributable to unsafe medical injections. 84 …”
Section: Unsafe Injection Practicesmentioning
confidence: 99%